PENGGUNAAN MEDIA PEMBELAJARAN PAPAN KATA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN PADA PELAJARAN BAHASA INDONESIA DI KELAS II SD NEGERI 101937 ADOLINA TAHUN PEMBELAJARAN 2024-2025 - Siti, Siti Mutiara; Dra. Rosmawati Harahap (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students' beginning reading skills through the use of word board learning media in Indonesian language lessons in grade II of SD Negeri 101937 Adolina in the 2024/2025 academic year. The background of this study is the low initial reading ability of students, indicated by their difficulty reading letters, syllables, and simple words. This study used the Classroom Action Research (CAR) method using the Kemmis and McTaggart model, implemented in two cycles, each consisting of planning, implementation, observation, and reflection. The research subjects were eight grade II students. The research instruments included observation sheets of teacher and student activities, as well as a reading skills test. Data were analyzed descriptively using quantitative and qualitative methods. The results showed a significant improvement in students' beginning reading skills. In Cycle I, the average achievement of student activities was 50%, categorized as poor. After improvements in Cycle II, this increased to 93%, categorized as excellent. Thus, the use of word boards has proven effective in creating a more engaging learning environment, increasing student participation, and improving beginning reading skills.